Bibliometric Analysis: Research Trends in The Use of Augmented Reality-Based Learning Media in Elementary Schools - Damayanti, Ika; Rahmadonna, Sisca; Andania, Ruqoyyah Amilia (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2024)
In the digital era, the use of digital learning media is increasingly popular among educators. The use of this media makes the trend of research on the use of digital learning media is increasing, including the use of Augmented reality which facilitates learning to be more real. This study aims to present data on the significance of bibliometric trends on Augmented reality as a learning media in elementary schools. The research method uses bibliometric analysis. Data analysis was carried out with the help of the VOSviewer application and biblioshiny with a total of 195 pieces of literature processed from the Scopus database from 2006-2024. The research results show that there was a significant increase in 2017 with 8 publications to a peak in 2020 with 24 publications but there was a decline again in 2021 with 15 publications. In 2021, the research discussion on this trend has decreased due to the fact that learning is no longer carried out by distance learning. Indonesia has contributed to this research although it is not dominant. Indonesia is one of the countries that has contributed research publications on this topic. China is the country with the most research citations. However, Indonesia should be more productive in writing on this topic, in order to make this trend increase.